The effect of fast eating on the thermic effect of food in young Japanese women - Toyama, Kenji; Zhao, Xifan; Kuranuki, Sachi; Oguri, Yasuo; Kashiwa(Kato), Eriko; Yoshitake, Yutaka; Nakamura, Teiji (International journal of food sciences and nutrition, 2015)
Abstract The relationship between eating speed and the thermic effect of food (TEF) remains unclear. We investigated the difference in the TEF when meals containing the same amount of energy were eaten in 5 min (fast eating) or 15 min (regular eating). Subjects were nine non-obese young women. Following a 350 kcal (1464 kJ) meal, energy expenditure and autonomic nervous system activity were measured. The frequency of mastication was also calculated. The TEF for the 15-min period after the start of eating with fast eating was significantly lower than with regular eating (p < 0.01). There was a significant positive correlation between the low-frequency/high-frequency ratio and TEF at 5-min intervals up to 20 min after the start of eating and between total mastication frequency and TEF during ingestion. Fast eating may reduce the TEF, potentially because a decrease in mastication frequency decreases sympathetic nervous system activity.